Magnitude and determinants of plant root hydraulic redistribution: A global synthesis analysis - Yang, Guisen; Huang, Lei; Shi, Yafei (Frontiers in Plant Science, 2022)
Plant root hydraulic redistribution (HR) has been widely recognised as a phenomenon that helps alleviate vegetation drought stress. However, a systematic assessment of the magnitude of HR and its drivers at the global scale are lacking. We collected 37 peer-reviewed papers (comprising 47 research sites) published in 1900–2018 and comprehensively analyzed the magnitude of HR and its underlying factors. We used a weighting method to analyze HR magnitude and its effect on plant transpiration. Machine learning algorithms (boosted regression trees) and structural equation modeling were used to determine the influence of each factor on HR magnitude. We found that the magnitude of HR was 0.249 mm H2O d-1 (95% CI, 0.113–0.384) and its contribution to plant transpiration was 27.4% (3%–79%). HR varied significantly among different terrestrial biomes and mainly occurred in forests with drier conditions, such as temperate forest ecosystems (HR=0.502 mm H2O d-1), where HR was significantly higher than in other ecosystems (p<0.01). The magnitude of HR in angiosperms was significantly higher than that in gymnosperms (p<0.05). The mean magnitude of HR first increased and then decreased with an increase in humidity index; conversely, the mean magnitude of HR decreased with an increase in water table depth. HR was significantly positively correlated with root length and transpiration. Plant characteristics and environmental factors jointly accounted for 61.0% of the variation in HR, and plant transpiration was the major factor that directly influenced HR (43.1% relative importance; p<0.001), and soil texture was an important indirect driver of HR. Our synthesis offers a comprehensive perspective of how plant characteristics and environmental factors influence HR magnitude.